Super Mario sign at somatostatin receptor PET/CT - Sharjeel Usmani; Khulood Al Riyami; Anjali Jain; Muneera Al Maraghy (Journal of the Pakistan Medical Association, 2024)
68Ga-DOTA NOC PET-CT imaging has been shown to have high accuracy for the evaluation of neuroendocrine tumours. We present the case of a 59-year-old male with well differentiated gastric neuroendocrine tumour (grade II) treated with surgery. 68Ga-DOTA NOC PET/CT was performed to rule out metastasis. 68Ga-DOTA NOC showed physiological uptake in the bilateral adrenal and horseshoe kidney appearing as the famous character Super Mario. There is no evidence of any abnormal somatostatin avid lesion. Keywords: 68Ga-DOTA NOC PET-CT, horseshoe kidney, neuroendocrine tumors, PET/CT